2018
DOI: 10.1038/s41566-018-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time full-field characterization of transient dissipative soliton dynamics in a mode-locked laser

Abstract: Dissipative solitons are remarkable localized states of a physical system that arise from the dynamical balance between nonlinearity, dispersion and environmental energy exchange. They are the most universal form of soliton that can exist in nature, and are seen in farfrom-equilibrium systems in many fields including chemistry, biology, and physics. There has been particular interest in studying their properties in mode-locked lasers producing ultrashort light pulses, but experiments have been limited by the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
199
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 330 publications
(213 citation statements)
references
References 61 publications
11
199
2
1
Order By: Relevance
“…For instance, the first, second, third, and fourth pulses are separated from the pulse group at about 1.5 × 10 5 , 2.5 × 10 5 , 3.8 × 10 5 , and 4.8 × 10 5 RTs, respectively. Note that the breathing dynamics with the period of ≈2.1 × 10 4 RTs is experimentally observed in this stage, similar to the previous report . Figure b, which is redrawn as the 3D picture from the data of the middle plot of Figure b, displays the evolution of stable fifth HML after about 5 min of the pump start‐up.…”
Section: Resultssupporting
confidence: 86%
“…For instance, the first, second, third, and fourth pulses are separated from the pulse group at about 1.5 × 10 5 , 2.5 × 10 5 , 3.8 × 10 5 , and 4.8 × 10 5 RTs, respectively. Note that the breathing dynamics with the period of ≈2.1 × 10 4 RTs is experimentally observed in this stage, similar to the previous report . Figure b, which is redrawn as the 3D picture from the data of the middle plot of Figure b, displays the evolution of stable fifth HML after about 5 min of the pump start‐up.…”
Section: Resultssupporting
confidence: 86%
“…Peregrine soliton in a wave tank (57) Draupner wave (1D propagation) in a wave tank (166) Modulation instability in optical fibre (47) Backgroundfree solitons in optical fibre (46) Rogue waves in supercontinuum generation (4) Full field measurements of turbulence and dissipative soliton transients (68,106) High order breathers in optical fibre (59) 2013 Current effects on rogue waves in a wave tank (157)…”
mentioning
confidence: 99%
“…It is wellknown that ultrashort solitons can form highly-stable bound-states, and these optical soliton molecules arise from balanced forces during propagation in passive fibers and in dissipative laser resonators [2][3][4][5]8,[16][17][18][19][20][21] . Recent real-time studies have revealed rapid transients, internal vibrations and even chaotic dynamics 6,7,[22][23][24] .In this study, we transfer the concepts of optical spectroscopy to the case of ultrafast soliton molecules by driving them with an external perturbation and monitoring their response in real time. We discover a resonance in the response of soliton molecules to external perturbation and probe the associated anharmonic binding potential (Fig.…”
mentioning
confidence: 99%